Awareness and Employment Impact Analysis in Cyber Security - Abdiyeva-Aliyeva, G.A. (Herald of Azerbaijan Engineering Academy, 2023)
The recent cyber wars and their consequences in the world, the available statistical data, lay the foundation for regular awareness raising in the field of cyber security. At the same time, in order to prevent incidents that occur, it should be one of the priority issues for specialists to simulate work impact analysis scenarios. The article gives is to explore the importance of raising awareness of cyber security threats and attacks, as well as the current challenges and solutions.